2019
DOI: 10.1111/liv.14120
|View full text |Cite
|
Sign up to set email alerts
|

Effect of direct‐acting antivirals on platelet‐associated immunoglobulin G and thrombocytopenia in hepatitis C virus‐related chronic liver disease

Abstract: Background & Aims Hepatitis C virus (HCV) infection has been known to cause various extrahepatic autoimmune disorders. The prevalence of platelet‐associated immunoglobulin G (PA‐IgG) has been high in patients with HCV infection. Because thrombocytopenia in HCV‐related liver diseases is a notable problem, we performed prospective study on the effect of direct‐acting antivirals (DAAs) treatment on PA‐IgG and platelet count. Methods A total of 215 patients with HCV‐related liver disease were enrolled in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 31 publications
(55 reference statements)
1
11
0
Order By: Relevance
“…Furthermore, it has been shown that about two-thirds of patients with HCV cirrhosis and clinically significant portal hypertension prior to antiviral therapy remain with this degree of portal hypertension 6 months after viral elimination 20. In further support of our study and providing an explanation for the results, a recent study by Honma et al performed in mostly non-cirrhotic patients with HCV demonstrated that PLT count increases significantly after viral eradication and that it correlated with a decrease in platelet-associated immunoglobulin G (PA-IgG), thereby implicating an HCVassociated immune mechanism in the genesis of thrombocytopenia 21. Therefore, our observation and that of others indicate that the increase in PLT observed in our study is most likely the effect of viral elimination itself and, importantly, indicates that scoring systems that include PLT count as one of the variables should not be used in the evaluation of the degree of fibrosis (or presence or absence of cirrhosis) in the post-SVR setting.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Furthermore, it has been shown that about two-thirds of patients with HCV cirrhosis and clinically significant portal hypertension prior to antiviral therapy remain with this degree of portal hypertension 6 months after viral elimination 20. In further support of our study and providing an explanation for the results, a recent study by Honma et al performed in mostly non-cirrhotic patients with HCV demonstrated that PLT count increases significantly after viral eradication and that it correlated with a decrease in platelet-associated immunoglobulin G (PA-IgG), thereby implicating an HCVassociated immune mechanism in the genesis of thrombocytopenia 21. Therefore, our observation and that of others indicate that the increase in PLT observed in our study is most likely the effect of viral elimination itself and, importantly, indicates that scoring systems that include PLT count as one of the variables should not be used in the evaluation of the degree of fibrosis (or presence or absence of cirrhosis) in the post-SVR setting.…”
supporting
confidence: 87%
“…In further support of our study and providing an explanation for the results, a recent study by Honma et al performed in mostly non‐cirrhotic patients with HCV demonstrated that PLT count increases significantly after viral eradication and that it correlated with a decrease in platelet‐associated immunoglobulin G (PA‐IgG), thereby implicating an HCV‐associated immune mechanism in the genesis of thrombocytopenia …”
Section: Discussionmentioning
confidence: 99%
“…Honma et al 19 prospectively studied 187 patients who were treated with direct-acting antivirals. PAIgG levels as well as Plt counts were measured prior to treatment and post-treatment.…”
Section: Auto-antibodiesmentioning
confidence: 99%
“…PA-IgG is frequently elevated in HCV-infected patients due to the presence of various autoantibodies [ 12 , 13 ]. Because ITP may be induced by HCV infection itself [ 14 , 15 , 16 ], HCV eradication with DAA may improve ITP [ 16 ]. The etiology of thrombocytopenia accompanying HCV infection is complex, requiring careful examination in individual patients.…”
Section: Discussionmentioning
confidence: 99%